(untitled) (Research, Society and Development, 2022)
The therapeutic properties of plants are as old as the occurrence of human species on Earth. Regardless of the purpose of the use of medicinal plants, there is no doubt that there has been an increase in demand for natural methods, representing a major challenge for producers and researchers, regarding standardization and quality control of the raw material, to ensure the quality of the species offered to consumers and the pharmaceutical industry. Despite the increased consumption and consequent expansion of the medicinal plants market, there are few specific studies involving the use of packaging and storage techniques for this type of product. Given the above, this study surveyed concepts involving packaging, as well as characteristics of some polymers commonly used in the storage of plant products, techniques and equipment used in the packaging of food products and work involving the use of modified atmosphere in the medicinal plants storage.